2015
DOI: 10.1001/jamapsychiatry.2015.0584
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofDSM-5Alcohol Use Disorder

Abstract: IMPORTANCE National epidemiologic information from recently collected data on the new DSM-5 classification of alcohol use disorder (AUD) using a reliable, valid, and uniform data source is needed.OBJECTIVE To present nationally representative findings on the prevalence, correlates, psychiatric comorbidity, associated disability, and treatment of DSM-5 AUD diagnoses overall and according to severity level (mild, moderate, or severe).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

55
917
11
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,166 publications
(1,080 citation statements)
references
References 66 publications
55
917
11
8
Order By: Relevance
“…Recent estimates of past‐year alcohol use disorder (AUD) are slightly higher than those for MD and AD at 13.9% (Grant et al., 2015), and prevalence of past‐year drug use disorders ranges between 2 and 3% (Merikangas & Mcclair, 2012). These disorders are associated with significant costs to the individual and society including: low levels of educational attainment, unstable employment, decreased work productivity, decreased health‐related quality of life, and increased primary care use (Donovan, Mattson, Cisler, Longabaugh, & Zweben, 2005; Kessler, 2012; Walley et al., 2012; Wittchen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates of past‐year alcohol use disorder (AUD) are slightly higher than those for MD and AD at 13.9% (Grant et al., 2015), and prevalence of past‐year drug use disorders ranges between 2 and 3% (Merikangas & Mcclair, 2012). These disorders are associated with significant costs to the individual and society including: low levels of educational attainment, unstable employment, decreased work productivity, decreased health‐related quality of life, and increased primary care use (Donovan, Mattson, Cisler, Longabaugh, & Zweben, 2005; Kessler, 2012; Walley et al., 2012; Wittchen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While alcohol use disorders (AUDs) are still prevalent within the U.S., young people are among the most affected [5]. The most recent National Epidemiologic Survey of Alcohol and Related Conditions (NESARC-III) found that young adults aged 18–29 have the highest past year and lifetime rates of AUDs [5]. This may be due, in part, to frequent heavy drinking among 15- and 16-year olds [2].…”
Section: Introductionmentioning
confidence: 99%
“…These results may be due to the fact that effect sizes for associations between discounting and severity of drug use are smaller than those typically found in comparisons of clinical populations to -non (Amlung, Vedelago, Acker, Balodis, & MacKillop, 2017); and thus the size of our relatively sub-clinical sample may not have been large enough to detect these particular associations. Finally, because problematic drug use is highly comorbid with other psychiatric conditions (Grant et al, 2015), our sample probably differed in other ways that impacted discounting (e.g., higher education).…”
Section: Discussionmentioning
confidence: 99%